Low dose oral beta-lactamase protects the gut microbiome from oral beta-lactam-mediated damage in dogs - Sheila Connelly; Brian Fanelli; Nur A. Hasan; Rita R. Colwell; Michael Kaleko (AIMS Press, 2019)
Antibiotics, while lifesaving, damage the gut microbiome and can precipitate proliferation of pathobionts. A strategy to preserve gut microbiome integrity is to eliminate biologically active antimicrobials excreted into the gastrointestinal tract (GI) without negatively affecting antibiotic therapeutic efficacy. Clinical proof of concept was achieved with SYN-004 (ribaxamase), a beta-lactamase enzyme formulated for oral delivery with intravenous penicillins and cephalosporins. Ribaxamase inactivated intestinal ceftriaxone, protected the gut microbiome, and significantly reduced the incidence of Clostridioides difficile disease. For use with oral beta-lactam antibiotics, a delayed release formulation of ribaxamase, SYN-007, was engineered for dissolution in the lower small intestine distal to the site of oral antibiotic absorption. In dogs that received oral amoxicillin, SYN-007 reduced microbiome disruption without interfering with amoxicillin systemic absorption. Here, a study to determine the lowest effective dose of SYN-007 was performed. Dogs received amoxicillin (40 mg/kg, PO, TID) +/- SYN-007 (PO, TID) at three doses, 10 mg, 3 mg, or 1 mg for five days. Serum amoxicillin levels, measured after the first and last antibiotic doses, were not significantly different +/- SYN-007 at all dose levels indicating that SYN-007 did not interfere with amoxicillin systemic absorption. Microbiome analyses demonstrated that amoxicillin significantly reduced bacteria richness and microbiome diversity resulting in altered microbiome composition. However, with all doses of SYN-007, microbiome richness and diversity were not significantly different from pretreatment and changes in microbiome composition were attenuated. These data demonstrate that effective SYN-007 doses can be reduced at least 10-fold while maintaining gut microbiome preservation. The potential to employ low SYN-007 doses to protect the gut microbiota has important implications for enhancing therapeutic outcomes for patients receiving oral beta-lactam antibiotics while simultaneously reducing cost per dose and ultimately, healthcare expenses.